The Existence of Customary Criminal Law within National Criminal Law after the Enactment of the New Criminal Code - Andronius Basado Siahaan; Abdul Rahman Maulana Siregar; Ismaidar Ismaidar; Martinus Bosko Sinaga; Sonya Evalin Br. Silalahi (The Future of Education Journal, 2026)
The existence of customary law in the reform of national criminal law is a critical issue within the context of Indonesia’s pluralistic legal system. As the indigenous law of the Indonesian people, customary criminal law is, in essence, an integral part of the Indonesian legal system. The reform of Indonesian cri minal law to replace colonial criminal law has accommodated customary criminal law as the basis for its legalization or recognition within the New Criminal Code (KUHP). This study examines the existence of customary criminal law within the national criminal legal system following the enactment of the new Criminal Code (Law No. 1 of 2023). This topic was chosen because it highlights the urgency of recognizing local legal values (living law) within the national system. The research employs a literature review method with a normative legal approach. These findings are crucial for strengthening the synergy between national law and local wisdom to foster an inclusive legal system.